1985
DOI: 10.1029/ja090ia12p12293
|View full text |Cite
|
Sign up to set email alerts
|

Observations of E region irregularities generated at auroral latitudes by a high‐power radio wave

Abstract: In September 1983 a series of ionospheric modification experiments was performed in Scandinavia using the high‐frequency (HF) heating facility located near Tromsø, Norway. The experiments were designed to study the production of geomagnetic field‐aligned irregularities in the auroral E region by a powerful HF radio wave. In this initial report, observations of 3.2‐m irregularities made with a mobile 46.9‐MHz field radar are presented. When ionospheric conditions are correct, irregularities having peak cross se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 35 publications
2
38
0
Order By: Relevance
“…In the work of Leyser et al [1989] it was reported that several of the prominent spectral features are absent when the applied frequency is near a harmonic of the electron gyrofrequency. After that, emphasis has been put on the possible role of smallscale magnetic field-aligned density striations, which are known to be generated in these experiments [Fialer, 1974;Minkoff et al, 1974;Djuth et al, 1985]. This overall view is strongly supported by later experimental findings, as will be further discussed in the next Gurevich et al, 1995].…”
Section: Introductionsupporting
confidence: 61%
“…In the work of Leyser et al [1989] it was reported that several of the prominent spectral features are absent when the applied frequency is near a harmonic of the electron gyrofrequency. After that, emphasis has been put on the possible role of smallscale magnetic field-aligned density striations, which are known to be generated in these experiments [Fialer, 1974;Minkoff et al, 1974;Djuth et al, 1985]. This overall view is strongly supported by later experimental findings, as will be further discussed in the next Gurevich et al, 1995].…”
Section: Introductionsupporting
confidence: 61%
“…This led to the generation of AFAIs, which scattered the 9-and 12-MHz signals used for Doppler diagnostics. It is believed [Djuth et al, 1985;Noble et al, 1987] that a thermal resonance instability at the upper hybrid (UH) level is the strongest candidate for the excitation of AFAIs in the E region.…”
Section: Observational Resultsmentioning
confidence: 99%
“…Djuth et al (1985) found from VHF radar observations during Tromsø HF heating experiments, that the generation of striations in the auroral E-region was possible when the heater frequency, f H , exceeded the critical frequency foEs by 0.2 MHz. The same result was obtained by Blagoveshchenskaya et al (1999Blagoveshchenskaya et al ( , 2006a when strong heaterinduced striations were observed in the auroral E-region with bi-static HF radio scatter.…”
Section: Introductionmentioning
confidence: 99%
“…The excitation of artificial small-scale field-aligned irregularities or striations (Minkoff et al, 1974;Djuth et al, 1985;Blagoveshchenskaya et al, 1999Blagoveshchenskaya et al, , 2006b), HF-induced electron heating (Rietveld et al, 2003) and airglow (Brandstrom et al, 1999;Pedersen and Carlson, 2001;Kosch et al, 2002), anomalous absorption (Robinson, 1989) and other phenomena occur at the upper hybrid resonance altitude in HF heating experiments when O-mode polarized HF pump waves reach the ionospheric reflection height. An O-mode HF pump wave couples through striations into electrostatic (upper hybrid) waves at the upper-hybrid resonance altitude, which is below the reflection height of the heating wave.…”
Section: Introductionmentioning
confidence: 99%